2004
DOI: 10.1038/sj.bjc.6602212
|View full text |Cite
|
Sign up to set email alerts
|

Fenretinide stimulates redox-sensitive ceramide production in breast cancer cells: potential role in drug-induced cytotoxicity

Abstract: The synthetic retinoid N-(4-hydroxphenyl) retinamide (4HPR) has manifold actions, which may contribute to its chemopreventive effects on breast cancer cell growth and progression. A role for ceramide as a stress-response signal is investigated here during the cytotoxic action of 4HPR in MCF-7 cells. N-(4-hydroxphenyl) retinamide induced a dose-dependent decline in cell growth and survival associated with a maximal 10-fold increase in ceramide production at 10 mM. N-(4-hydroxphenyl) retinamide exhibited a great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 25 publications
1
33
0
3
Order By: Relevance
“…For example, the chemotherapeutic agents fenretinide and anandamide were shown to induce ceramide production through activation of ASMase (36,37). However, other reports showed that ceramide generated by these agents can be blocked by fumonisin B1 treatment (38,39). In some cases, there were different results reported for the same cell line.…”
Section: Discussionmentioning
confidence: 42%
“…For example, the chemotherapeutic agents fenretinide and anandamide were shown to induce ceramide production through activation of ASMase (36,37). However, other reports showed that ceramide generated by these agents can be blocked by fumonisin B1 treatment (38,39). In some cases, there were different results reported for the same cell line.…”
Section: Discussionmentioning
confidence: 42%
“…A role for caspase-8 and caspase-9 in 4-HPR action has also been reported (19,20). In human neuroblastoma and MCF-7 cells, pan-caspase inhibitors (BOC-d-fmk and z-VAD-fmk, respectively) were shown to significantly reduce apoptosis after 4-HPR treatment (24,44). In Fas-defective hepatoma cells, the general caspase inhibitor z-VAD-fmk completely blocked apoptosis in response to 4-HPR (20).…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism whereby single agent 4-HPR has been reported to induce apoptosis and/or necrosis in cancer cells is via the increase of ceramides (21,22,30,31,40,41). However, because many studies used less precise TLC methods that could not provide in-depth structural information, it was not known which particular sphingolipid subspecies were elevated.…”
Section: Discussionmentioning
confidence: 99%